Straight talk about children and sport. Advice for parents, coaches, and teachers - LeBlanc, J.; Dickson, L. (1996)
Straight Talk About Children And Sport provides some important information about the early developmental needs of young children in organized sport. It focuses on children between the ages of six and 12 years, a time when they are most likely to be introduced to sport. Because all children develop at different times and at different rates, the ages used in the book are provided only as a general guideline.